Sokora's Kecapi as Performing Art of The Geneology Study of Assimilation Art in Identity Mukomuko Aristocratic Community - Parmadil, Bambang; -, Bernardin; Muktadir, Abdul; -, Wembrayarli (Institut Seni Indonesia Denpasar, 2023)
The dynamics exposed to the traditional music of the Mukomuko coast in Bengkulu province have made researchers interested in uncovering the genealogy of the identity of the Sokora lute. Sokora lute art as a result of cultural assimilation from outside (Gujarat/India) of the people of the coastal city of Mukomuko has become local traditional music with local cultural wisdom values, both in the sociocultural context and in performances. Cultural assimilation and acculturation play an important role in making Sokora a traditional art in Mukomuko City. The word Kecapi Sokora itself comes from the word mancubo or roughly in the mukomuko dialect. This research is a qualitative phenomenological research type. Research that emphasizes more aspects of the description or description of the object being observed. Research with this qualitative approach seeks to understand and provide in-depth information both contextually and factually. The research was conducted to understand and explain the phenomena that have been going on and are being carried out as well as to provide information on knowledge about the transformation of local cultural wisdom values of traditional music of the Bengkulu coastal community. Based on qualitative methods and a cultural studies approach, this research emphasizes exploring, traveling, explaining, and describing ethically, emically, and holistically. Genealogically, at first Kecapi Sokora was a form of solo music and oral literature that was developed in Mukomuko, especially among the nobility. The Sokora Harp Performance is an art that is characteristic of the aristocratic society in Mukomuko at the time when the Mukomuko port was still a transit center for traders from outside, especially from Gujarat India in ancient times. The word Kecapi Sokora itself comes from the word mancubo or roughly in the mukomuko dialect. The Sokora Kecapi instrument is one of the melodic instruments in its class, including the chordophone, which means that the sound source comes from strings or strings. The tones of the Sokora Kecapi instrument consist of seven notes in the following order, 1, 2, 3, 4, 5, 6, and 7 which are called diatonic. In terms of scale, the Kecapi Sokora is unique from other forms of traditional musical instruments, where the tones of traditional musical instruments are usually pentatonic (five tones). The Performing Arts of Kecapi Sokora is one of the traditional arts in Mukomuko. The art of Kecapi Sokora Mukomuko as a traditional art of the Mukomuko nobility consists of a series of Malay musicality and dances accompanied by percussion drums and vocal/speech instruments. In the show, the Sokora Mukomuko lute art, the duration of the performance is determined by the number of requests for speech/poem and dance performances.